Beyond methodological agnosticism: Ritual, healing, and Sri Lanka's civil war - Hatsumi, Kaori (The Australian journal of anthropology, 2017)
In April 2010, eleven months after the end of Sri Lanka's civil war, I participated in the Catholic Easter rite in a Tamil fishing village in the Vanni, where the last battle between the Sri Lankan government forces and the Liberation Tigers of Tamil Eelam was fought. This article explores the way in which the ritual enactments of the paschal mystery, called pasch, came to have enormously therapeutic effects for the survivors during Holy Week. The decisive factors in the villagers’ Easter experience included: the nature of the orthodox rite and accompanying local traditions, the unique historical context in which they found themselves, and their readiness to receive healing and start a new life. The article calls for the abandonment of methodological agnosticism in order for us to understand the villagers’ religious experiences, and contributes to the emerging field of ‘post-secular’ anthropology.